Socioeconomic characteristics of patients evaluated for liver transplantation in a tertiary center - Eva Almaraz-Arriaga; Víctor Manuel Páez-Zayas; Liz Nicole Toapanta-Yanchapaxi; Alejandra Rosales-Fernández; Ignacio García-Juárez (Instituto Nacional de Salud Pública, 2018)
[Not available]